2005
DOI: 10.1111/j.1741-3729.2005.00340.x
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed Methods Study of Refugee Families Engaging in Multiple‐Family Groups*

Abstract: This study investigated family factors and processes involved in Bosnian refugees engaging in multiple-family support and education groups in Chicago. Families that engaged experienced more transitions, more traumas, and more difficulties in adjustment. Engagement strategies for multiple-family groups should correspond with the underlying family processes by which refugee families manage transitions, traumas, and adjustment difficulties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 23 publications
0
46
0
Order By: Relevance
“…Different forms of service or training of workers would be possible in a resettlement agency, a school, a church, or a clinic, which are the most common places for psychosocial work with refugees and immigrants. It is important to remember that most refugees and immigrants do not identify family therapy or mental health as a need, so how to engage them is often the principal challenge (Weine et al, 2005). …”
Section: Discussionmentioning
confidence: 99%
“…Different forms of service or training of workers would be possible in a resettlement agency, a school, a church, or a clinic, which are the most common places for psychosocial work with refugees and immigrants. It is important to remember that most refugees and immigrants do not identify family therapy or mental health as a need, so how to engage them is often the principal challenge (Weine et al, 2005). …”
Section: Discussionmentioning
confidence: 99%
“…Programs developed specifically for refugee and immigrant youth often demonstrate innovative strategies for engaging families. Strategies that have shown particular promise include engaging the cultural community in the development of services (Measham, Rousseau, & Nadeau, 2005;Weine, Ware, & Klebic, 2004;Weine et al, 2005); locating mental health services within nonstigmatized service systems such as schools (Jaycox, 2004;Kataoka et al, 2003;Rousseau & Guzder, 2008;; developing partnerships among providers, educators, and the community ; and integrating services (Watters, 2001;Watters & Ingleby, 2004; see Figure 1). …”
Section: Strategies For Addressing Barriersmentioning
confidence: 97%
“…In these programs, family engagement strategies included encouragement, the use of "affirmative idioms" during recruitment, and identifying and problem-solving barriers to participation. In addition, these programs were located in the community and run by ethnically matched facilitators (Weine et al, 2005;Weine et al, 2003). Research on these programs has demonstrated that these strategies increase family engagement and access to mental health services (Weine et al, 2008).…”
Section: Engaging Family and Communitymentioning
confidence: 99%
“…Eight key intervention characteristics were identified through the developmental and intervention studies in our prior research (Weine, 2001, 2008a, 2008b, 2009; Weine et al, 2000, 2003, 2005, 2006, 2008; Weine, Ware, & Lezic, 2004; Table 2). …”
Section: Key Intervention Characteristics Of Preventive Interventionsmentioning
confidence: 99%